2023
DOI: 10.1039/d3ta04520j
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress and perspectives on heteroatom doping of hematite photoanodes for photoelectrochemical water splitting

Juhyung Park,
Jihun Kang,
Sourav Chaule
et al.

Abstract: Over the past few decades, extensive research on photoelectrochemical (PEC) water splitting has been conducted as a promising solution to meet the increasing demand for cleaner and renewable energy in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Generally, the PEC efficiency is evaluated by the efficiencies of light harvesting, charge transfer, and surface reaction. 2 UV/Vis diffuse reflectance spectroscopy (DRS) revealed that FeNi(OH) X had a trivial effect on light harvesting (Fig. S22†), suggesting that the improved PEC performance can be mainly ascribed to charge transfer and surface catalysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the PEC efficiency is evaluated by the efficiencies of light harvesting, charge transfer, and surface reaction. 2 UV/Vis diffuse reflectance spectroscopy (DRS) revealed that FeNi(OH) X had a trivial effect on light harvesting (Fig. S22†), suggesting that the improved PEC performance can be mainly ascribed to charge transfer and surface catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…Solar-driven photoelectrochemical (PEC) water splitting has been broadly regarded as a promising solution for sustainable and decarbonized technology in the quest of green and renewable energy. 1–7 Since TiO 2 photoanodes, researched by Fujishima and Honda, 8,9 were employed to perform water splitting to produce hydrogen, a majority of semiconductors, for example, TiO 2 , 10 α-Fe 2 O 3 , 11–14 Ta 3 N 5 , 15,16 and BiVO 4 , 17–22 have been regarded as ideal photoanodes for PEC water splitting in recent years. Among various candidates, BiVO 4 is the most promising candidate for PEC water oxidation because of a low bandgap (2.4 eV), low cost, and ideal band-edge positions.…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that the N ss distribution of Fe 2 O 3 was extended to the inner conduction band (CB), leading to an increase in photogenerated electron and hole recombination and the triggering of the deleterious Fermi energy level pinning occurring at N ss and more negative potential values. 38,51,52 However, the N ss center of the Fe 2 O 3 /MoO 3 -350 photoanode was closer to the thermodynamic value of oxygen precipitation (1.23 V RHE ), which was more conducive to the transport of holes and significantly reduced the carrier recombination problem of the Fe 2 O 3 photoanode, promoting surface water oxidation.…”
Section: Mechanistic Investigation Via Peismentioning
confidence: 95%
“…7 Some of the most intensely investigated photoanodes are based on passivated high-quality semiconductors ( e.g. , Si or III–V compounds), 8–10 hybrid inorganic–organic architectures, 11–14 or on low-cost metal oxides, such as Fe 2 O 3 , 15,16 CuWO 4 17,18 or BiVO 4 . 3,19–27 In particular, BiVO 4 is an attractive material owing to its bandgap energy of ∼2.4 to 2.6 eV, which translates to the maximum theoretically achievable photocurrents of 6.4–8.9 mA cm −2 and the solar-to-hydrogen (STH) efficiencies of 8–11% under AM 1.5G (1 sun) illumination.…”
Section: Introductionmentioning
confidence: 99%